Effects of nitric oxide synthesis on reperfusion injury and catecholamine responsiveness in a heterotopic rat heart-transplantation model - Szabó, Gábor; Bátkai, Sándor; Bährle-Szabó, Susanne; Dengler, Thomas; Vahl, Christian-Friedrich; Zimmermann, Rainer Johannes; Hagl, Siegfried (Journal of cardiovascular pharmacology, 1998)
Global myocardial ischemia and reperfusion injury play a major role in early postoperative graft dysfunction. In this study, the influence of nitric oxide (NO) on reperfusion injury and catecholamine sensitivity after ischemia was investigated in a heterotopic rat heart-transplantation model. After a 1-h ischemic preservation, reperfusion was started either after application of saline vehicle (control, n = 8) or nitro-L-arginine methyl ester (L-NAME; 10 mg/kg, n = 8) for inhibition of NO synthesis or NO-precursor L-arginine (L-Arg; 40 mg/kg, n = 8), or L-NAME plus L-Arg (n = 8), respectively. After 60 min of reperfusion, continuous dobutamine infusion (5 μg/kg/min) was started. Myocardial blood flow was assessed by the hydrogen-clearance method. An intraventricular balloon was used to measure pressure-volume relations: peak left ventricular pressure, the rate of pressure development (dP/dt), end-diastolic pressure, and isovolumic relaxation constant. Myocardial blood flow was significantly reduced after L-NAME and increased after L-Arg in comparison with control (p < 0.05). The L-NAME group showed decreased systolic and diastolic functional recovery in comparison with control. Simultaneous infusion of L-Arg and L-NAME reversed these effects. L-Arg alone led to a further improvement of cardiac functional recovery. Whereas myocardial blood flow remained unchanged in the L-NAME group with dobutamine infusion, it significantly increased in the control group (p < 0.05). L-Arg antagonized this effect of L-NAME. Dobutamine increased peak left ventricular pressure and dP/dt and shortened the isovolumic relaxation constant in all groups; however, the changes of systolic hemodynamic indices were significantly smaller in the L-NAME group (p < 0.05) and significantly higher in the L-Arg group (p < 0.05). These results indicate that (a) NO production within the graft during reperfusion has a significant beneficial effect on graft function, and (b) NO formation may play an important role in β-adrenergic responses after heart transplantation.
Gesehen am 16.06.2025